Pengembangan media audio visual terhadap pemahaman konsep IPAS kelas 5 SDN 247 Palembang - Siti Safira Asyasiah; Lukman Hakim; Lefudin (COLLASE (Creative of Learning Students Elementary Education), 2026)
This study aims to develop audio-visual media in learning Natural and Social Sciences (IPAS) for fifth grade elementary school students that are valid, practical and have a potential effect on improving students' conceptual understanding. The background of this study is based on the difficulties often experienced by teachers and students in conveying and understanding abstract and complex IPAS concepts, such as the material "Getting to Know the Earth". The available learning media tend to be monotonous and do not facilitate the cognitive needs of students who are at the concrete operational stage. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The validity of the media was tested by material experts, media experts, and IPAS teachers, while practicality was assessed through limited and extensive trials in elementary schools. The effectiveness of the media was tested through a pretest-posttest test. The results of the study showed that the audio-visual media developed was in the very valid category (mean validation score> 85%), practical for use by teachers and students (mean practicality score> 80%), and had a potential effect on improving understanding of IPAS concepts, as evidenced by a significant increase in posttest scores. Thus, this audio-visual media is worthy of being used as an alternative for learning science in elementary schools to help students understand concepts in a more concrete, interesting, and meaningful way.